The American Convention on Human Rights and the marriage of same-sex couples in Ecuador: a reading from a material concept of the Constitution - Storini, Claudia (2019)
In this work, we seek to provide the reader with legal elements regarding the material concept of the Constitution, and from its configuration, analyze equal marriage in Ecuador. The text has been divided into three parts; in the first part, reference is made to advisory opinions and their legal value in the Inter-American System for the Protection of Human Rights; in a second, the value of said advisory opinions in Ecuador is observed from the understanding of the material concept of its Constitution; and finally, the institution of equal marriage in Ecuador and its full recognition based on analysis of the material concept of the Ecuadorian Constitution of 2008. In short, we try to address equal marriage in Ecuador with total legal objectivity, based on academic rigor and a clear understanding of human rights in its normative dimension.